Some aspects of biology of the bar-eyed goby Glossogobius giuris (Hamilton 1822) (Perciformes: gobiidae) from Netrakona - Saha, Bimal Kanta; Hassan, Md Fuad; Saha, Aparna (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The investigation was conducted on some aspects of biology viz. morphometrics, meristics, length-weight relationship and coefficient of condition of the Bar-eyed goby Glossogobius giuris. The mean of total length (TL) (94.42 ± 18.52 mm), standard length (SL) (73.13 ± 3.45mm), pre-dorsal length (PDL) (28.8 ± 7.32mm), head length (HL) (23.9 ± 4.87mm), snout length (SnL) (8.15 ± 1.9 mm) and height of body (HB) (14.17 ± 3.29mm) were determined.The relationships between the total length and other body parameters were found to be positively correlated and highly significant. The fin formula is D1.6; D2.1/9-10; P1.17-21; P2.1/5; A.1/9; C.17. The length-weight relationships of combined sex of G. giuris were determined as Log TW = -4.802 + 2.857 Log TL. The coefficient of conditions from the ko of combined sex and from the kc of combined sex was determined as 0.834 ± 0.132 and 0.827 ± 0.027, respectively. Kn values of combined sex were found to be 1.001 ± 0.156. J. Asiat. Soc. Bangladesh, Sci. 42(1): 95-106, June 2016